Digital tools for the dissemination and strengthening of maritime awareness - Roby Nivelo, Arturo José (2021)
This work describes an experience using digital tools to improve technical-pedagogical processes of one of the symbolic objectives of the General Directorate of Maritime Interests (DIGEIM): To disseminate and strengthen national maritime awareness. The project flowed through four stages: diagnosis, capacity building, identification of digital tools, and quantitative and qualitative evaluation. Given how particular and at the same time transcendental it is for DIGEIM to strengthen maritime awareness within the framework of its institutional objective, and given the new labor reality in force in all areas due to the COVID-19 crisis, the work provides sufficient examples to understand and replicate the experience in other contexts, mainly those related to coastal marine environmental education.